Chalk in Hand: The Draw and Tell Book - Pflomm, Phyllis Noe (Rowman & Littlefield Publishers, 1993)
This is a book for anyone who tells stories—teachers, parents, and especially children's librarians. Although the storyteller must draw during the presentation, artistic ability is not necessary for success. All stories and poems in this collection of stories and poems with chalk-board drawings have been tested in library story hours and in visits to schools. Several are intended for the pre-kindergarten age group, and most are suitable for older children as well.